A review on constructs of the practices of quality management - Tan, Chin Keng; Abdul Rahman, Hamzah (Academic Journals, 2011)
Quality management is a management function that ensures the quality of the products, services and/or operation processes of an organization. It contributes to the competitiveness and maintains the sustainability of the organization. This paper reviews the constructs of practices of quality management adopted by researchers. Based on the literature review, the practices of quality management are summarized into eight constructs. They are approaches, methods, tools and techniques, management commitment, quality attitude and culture, customer focus, human resource management, supplier relationship, cost of quality, measurement, information and analysis, and continuous improvement and sustainability.